Identification of long non-coding RNA ZFAS1 as a novel biomarker for diagnosis of HCC. Issue 4 (18th July 2018) - Luo, Ping; Liang, Chunzi; Zhang, Xianwei; Liu, Xuefang; Wang, Yingchao; Wu, Mengmeng; Feng, Xiaobo; Tu, Jiancheng
Abstract : Hepatocellular carcinoma (HCC) is the third major cause of cancer-related deaths. Abundant research show that long non-coding RNAs (lncRNAs) play critical roles in the initiation and progression of HCC and may serve as diagnostic markers for HCC. In the present study, six lncRNAs were chosen as candidate genes on the basis of previous literature to evaluate their diagnostic value on HCC by qRT-PCR. Experiment was first carried out in 22 pairs of tissues from HCC and then those were differently expressed in tissues were further tested in plasma from 20 HCC patients and 20 control cases. At last, ZFAS1 was chosen to be further analyzed in another 214 plasma samples including 79 control cases, 75 hepatitis B and cirrhosis patients, and 60 HCC patients. The levels of plasma ZFAS1 in HCC were significantly higher than those in healthy controls ( P <0.001), and in patients with cirrhosis and hepatitis B ( P <0.001), and was positively associated with serum α-fetoprotein (AFP). Meanwhile, the area under the receiver operating characteristic curve (AUC) of ZFAS1 was 0.801 to diagnose HCC from healthy controls, while AFP was 0.798 and the combined AUC of ZFAS1 and AFP was 0.891 (95% CI: 0.829–0.953), slightly higher than ZFAS1 alone. In conclusion, our results indicated that ZFAS1 could serve as a biomarker for diagnosing HCC.